Resonance Raman scattering from heme o complexes and cytochrome bo 3 oxidase - Wu, Wengan; Chang, Chi; Varotsis, Constantinos (My University, 1999)
The cytochromes b03 and bd are the terminal ubiquinol oxidases in the anaerobic chain of Escherichia coli. As deduced from its gene structure in E. coli, cytochrome b03 is strongly related to the superfamily of heme-copper containing enzymes. In particular, the enzyme catalyzes the two-electron oxidation of ubiquinol and the four-electron reduction of O2 to H20 and it couples the free energy of these electron-transfer processes to translocate protons on the periplasmic side of the membrane. Cytochrome b03 contains a six-coordinated, low-spin b-type heme; a five-coordinated, high-spin oxygen-binding otype heme; and one copper atom (CUB). The heme 0 is structurally related to heme a with a methyl residue replacing the formyl group at pyrrole ring D [1]
Keywords: Cytochromes; Heme; Escherichia coli; Copper; Enzymes; Protons; Chemistry